Hospital universitário Um sonho... uma conquista... uma realidade... - Siqueira, Hedi C. Heckler de; Laurino, Lavieira Bessouat; Lavoratti, Maria Antonieta; Netto, Zulma Guimarães (VITTALLE - Revista de Ciências da Saúde, 2017)
Ver no documento